Preparation method of graphene composite carbon spheres

The preparation of graphene composite carbon spheres through the template-free emulsification, dispersion, condensation and curing process has solved the problems of low production capacity, high cost and low density of existing graphene spheres, and achieved high thermal conductivity, high electrical conductivity, and isotropic porous carbon sphere preparation, reducing production costs.

CN119873810AActive Publication Date: 2025-04-25XIAN ANJUDE NANO TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510014152.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing graphene spheres have low production capacity, high cost, low density, low thermal conductivity and electrical conductivity, and the two-dimensional shape of graphene is easily affected by the process and cannot reach a disordered state.

Method used

The emulsification, dispersion, condensation and curing process without templates is used, asphalt and phenolic resin are used as binders, graphene or graphene oxide and graphite powder are added, and graphene composite carbon balls are prepared after heating and drying and high temperature carbonization to control their density and average particle size.

Benefits of technology

Isotropic porous carbon spheres with high thermal conductivity and high electrical conductivity were prepared, with controllable density and an average particle size range of 30-150μm. They are suitable as modification additives to improve thermal conductivity and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873810A_ABST
    Figure CN119873810A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a graphene composite carbon sphere, which is characterized in that the graphene composite carbon sphere is an isotropic porous carbon sphere with high thermal conductivity and high conductivity, the raw materials of the graphene composite carbon sphere are graphene, graphene oxide and graphite powder, and the adhesive is asphalt and amine curing type thermal shrinkage phenolic resin. The graphene composite carbon spheres are prepared by adopting template-free low-cost emulsification, dispersion, condensation, solidification and granulation, heating, drying and high-temperature carbonization, the density of the graphene composite carbon spheres is 0.3-1.5 g / cm < 3 >, and the average particle size range is 30-150m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a graphene composite carbon ball, and in particular to a method for preparing a graphene composite carbon ball with high thermal conductivity, high electrical conductivity, light weight and high strength. Background Art

[0002] Graphene has been popularized and applied in rubber and plastic as a thermal and electrical conductive additive. As a two-dimensional material, graphene also modifies and enhances the composite properties of other materials in two dimensions, that is, the enhancement effect in the in-plane direction is obvious, and the performance perpendicular to the plane is reduced by 2 or 3 orders of magnitude. In quite a few applications, isotropic modification and enhancement is required, rather than anisotropic. Therefore, it has become an important method to make graphene disordered and arbitrarily oriented in the enhanced continuous phase through various process means. However, the two-dimensional shape of graphene is easily affected by the process orientation. In the state of high thermal conductivity and high electrical conductivity with high graphene concentration, graphene particles interfere with each other and cannot reach a disordered state.

[0003] As a new material, graphene spheres have a wide range of application scenarios. In addition to being an additive for non-extractive thermal and electrical conductive materials, they can also be used as negative electrode materials for lithium batteries and supercapacitors. There are many methods to produce graphene spheres, such as using spherical templates to prepare graphene spheres, emulsifying graphene spheres, spraying graphene spheres, etc. The existing process for producing graphene spheres has low production capacity, high cost, low density, low thermal conductivity and low electrical conductivity. Summary of the invention

[0004] To solve the above problems, the purpose of the present invention is to provide a three-dimensional graphene composite carbon sphere as a modified additive, the additive is isotropic, and will not follow the process orientation during the production process to form anisotropy of the product, and the density is controllable (porosity is controllable). The main raw material is industrial-grade low-cost raw material, which is easy to achieve large-scale production.

[0005] The present application provides a method for preparing graphene composite carbon spheres, wherein the graphene composite carbon spheres are isotropic porous carbon spheres with high thermal conductivity and high electrical conductivity, and the raw materials of the graphene composite carbon spheres include: graphene and / or graphene oxide, graphite powder, and a binder;

[0006] The adhesive is asphalt and amine-cured heat-shrinkable phenolic resin, which is prepared by emulsification, dispersion, condensation, curing and granulation without template, and then subjected to heating, drying and high-temperature carbonization;

[0007] The density of the graphene composite carbon sphere is 0.3-1.5 g / cm 3 , the average particle size ranges from 30 to 150 μm.

[0008] Optionally, the adhesive raw materials include: butanol, phenolic resin, asphalt;

[0009] The raw material formula ratio of the graphene composite carbon ball is asphalt: phenolic resin: graphene or graphene oxide: graphite powder: butanol, and the weight ratio is 100:30-150:50-200:100-200:30-150.

[0010] Optionally, the raw material formula ratio of the graphene composite carbon ball is asphalt: phenolic resin: graphene or graphene oxide: graphite powder: butanol in a weight ratio of 100:40-110:50-110:110-150:40-70.

[0011] Optionally, the formula of the emulsified dispersed aqueous solution is: the weight ratio of deionized water: hexamethylenetetramine: polyvinyl alcohol is 100: 2-10: 0.5-3;

[0012] Optionally, the formula of the emulsified dispersed aqueous solution is: the weight ratio of deionized water: hexamethylenetetramine: polyvinyl alcohol is 100: 3-7: 0.5-3;

[0013] 20 to 40 liters of graphene composite solution are emulsified with 100 liters of aqueous solution.

[0014] Optionally, the softening point / melting point of the adhesive asphalt and phenolic resin is 70-80°C, and they can be melted and stirred and evenly mixed together at high temperature;

[0015] The curing agent of the phenolic resin is hexamethylenetetramine, which is dissolved in deionized water to form an emulsified dispersed aqueous solution, and undergoes a condensation curing reaction with phenolic resin at the emulsified interface during dispersion;

[0016] The graphene or graphene oxide has a particle size range of 5 to 30 μm, an aspect ratio of better than 1000, and the graphite powder is fine powder with a mesh size greater than 800 meshes.

[0017] Optionally, the graphene or graphene oxide has a particle size range of 7 to 15 mm.

[0018] Optionally, the preparation method comprises the following steps:

[0019] (1) preparing graphene slurry: heating asphalt and thermoplastic phenolic resin to form a mixed solution, adding graphene or graphene oxide powder and graphite powder to form a uniform slurry, adding n-butanol, adjusting the viscosity, and forming an emulsifiable slurry;

[0020] (2) dissolving polyvinyl alcohol and hexamethylenetetramine in deionized water and stirring uniformly to form a dispersed aqueous solution;

[0021] (3) introducing the dispersed aqueous solution into a high-speed emulsification dispersion kettle, heating it to 90°C, stirring at a high speed, with the linear speed of the stirring and dispersing disk being greater than 20 m / s, introducing the prepared 90°C graphene slurry, and emulsifying it, adjusting the emulsification conditions, and controlling the emulsified particle size of the slurry. The faster the speed, the smaller the average particle size, and the slower the speed, the larger the average particle size.

[0022] (4) Continuously stirring at high speed, the phenolic resin gradually condenses and solidifies under the catalytic action of hexamethylenetetramine to form a three-dimensional network structure, forming an insoluble and infusible composite ball, and the condensation reaction time is 60 to 240 minutes;

[0023] (5) centrifugally dehydrating and filtering to obtain a composite spherical powder wet cake;

[0024] (6) drying at 150° C. and crushing to obtain composite powder;

[0025] (7) carbonizing the composite powder in an inert atmosphere furnace to obtain graphene composite carbon powder, the carbonization temperature is 700 to 1500° C., and the carbonization time is 60 to 240 min;

[0026] (8) The slightly agglomerated composite powder is crushed by a pulverizer to obtain graphene composite carbon spheres with controllable particle size.

[0027] Optionally, the production equipment is an industrial-grade mixer, an emulsifying disperser, a dehydrator, a dryer, a carbonizing furnace and a pulverizer / crusher to form a large-scale continuous production system.

[0028] Optionally, the graphene composite carbon spheres are compounded with rubber and plastic to improve electrical conductivity and thermal conductivity, and the electrical conductivity of the composite material compounded with nylon is 5 to 500 S / m.

[0029] The present invention also provides a production equipment system for preparing isotropic thermally conductive, electrically conductive, lightweight and high-strength graphene composite carbon microspheres. The production equipment includes a conventional heating reactor, a high-speed emulsifier, a centrifugal dehydrator and a crawler-type continuous dryer, a high-speed powder pulverizer and a continuous or intermittent carbonization furnace, which can easily realize continuous large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the production equipment and process flow of the graphene composite ball powder of the present invention;.

[0031] Figure 2 This is a photo of graphene composite carbon spheres produced using the present invention.

[0032] Figure 3 This is a cross-sectional view of a flat plate prepared by combining graphene-composite carbon spheres with nylon.

[0033] Figure numerals: In the figure: 1 spiral ribbon stirring mixing kettle, 2 liquid mixing tank, 3 emulsifying kettle, 4 continuous dehydrator, 5 continuous crawler dryer, 6 crusher 1, 7 continuous crawler carbonization furnace, 8 crusher. DETAILED DESCRIPTION

[0034] The content of the present invention is described in more detail below in conjunction with the embodiments. It should be noted that the following embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the following embodiments, and there are also many variations. All variations directly derived or associated from the content disclosed in the present invention should be considered as the protection scope of the present invention.

[0035] In the present invention, unless otherwise specified, all parts and percentages are by weight, and all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are conventional methods in the art unless otherwise specified.

[0036] Specifically, the inventor provides the following technical solution:

[0037] The present invention first provides a process for preparing isotropic thermally conductive, electrically conductive, lightweight and high-strength graphene composite carbon microspheres. Asphalt with a melting point / softening point of 70 to 80°C is mixed with a thermoplastic phenolic resin with the same softening point to form a mixed solution. Graphene or graphene oxide powder and graphite powder with a mesh size of 800 or more are added to form a uniform slurry. The particle size of graphene and graphene oxide is in the range of 5 to 30 μm, preferably 7 to 15 μm, and the aspect ratio is better than 1000. N-butanol is added to adjust the viscosity to form an emulsifiable slurry. Polyvinyl alcohol and hexamethylenetetramine are dissolved in deionized water in a mixing tank and stirred evenly. The aqueous solution is introduced into a high-speed emulsification and dispersion kettle, heated to 90°C, stirred at a high speed, and the linear speed of the stirring and dispersing disk is greater than 20 m / s. The prepared slurry is introduced and emulsified, and the emulsification conditions are adjusted to control the emulsified particle size of the slurry. The fast speed leads to a small average particle size, and the slow speed leads to a large average particle size. Under the catalytic action of hexamethylenetetramine, the phenolic resin gradually condenses and solidifies to form a three-dimensional network structure, forming an insoluble and infusible composite ball. The condensation reaction time is 60 to 240 minutes. The composite spherical powder wet cake is obtained by centrifugal filtration, dried at 150°C, and dispersed to obtain a composite spherical powder. The composite spherical powder is carbonized in an inert atmosphere continuous furnace to obtain graphene composite carbon spherical powder. The carbonization temperature is 700 to 1500°C, the carbonization time is 60 to 240 minutes, and the density of the composite powder is 0.3 to 1.5 g / cm 3 The average particle size ranges from 30 to 150 μm. The higher the temperature, the higher the thermal conductivity and electrical conductivity of the spherical powder.

[0038] The present invention further provides a production formula for isotropically heat-conductive, electrically-conductive, lightweight and high-strength graphene composite carbon microspheres. The ratio of the graphene resin composite solution is asphalt: phenolic resin: graphene: graphite powder: butanol in a weight ratio of 100:30-150:50-200:100-200:30-150. The ratio of the curing agent aqueous solution is deionized water: hexamethylenetetramine: polyvinyl alcohol in a weight ratio of 100:2-10:0.5-3, preferably 100:3-7:0.5-3. 100 liters of the aqueous solution can emulsify 20-40 liters of the composite solution. Asphalt composed of polycyclic aromatic hydrocarbons easily forms a graphene structure after carbonization, and forms a highly thermally and electrically conductive structure with graphite powder and graphene, but melts during the carbonization process, requiring a special non-melting process to ensure that the asphalt ball particles are independently carbonized. The addition of phenolic compound formula forms insoluble and non-melting graphene + graphite powder + phenolic + asphalt composite particles during the curing process, and the morphology is stable during the drying and carbonization process. Adding graphite powder can reduce costs, and at the same time, the aspect ratio of graphite powder is low, and it is easier to form a disordered structure.

[0039] Graphene composite carbon balls are mixed with thermoplastic powders such as nylon powder and hot pressed into thermal and electrical conductive parts with a density of 0.6 to 1.3 g / cm 3 , conductivity 5~500S / m.

[0040] Example 1

[0041] like Figure 1As shown, the present invention first provides a method for preparing isotropic thermally conductive, electrically conductive, lightweight and high-strength graphene composite carbon microspheres, heating the mixing kettle to 90°C, adding asphalt with a melting point / softening point of 70 to 80°C and thermoplastic phenolic resin, such as Shengquan's phenolic resin, stirring to form a uniform mixed solution, adding graphene or graphene oxide powder and graphite powder above 800 mesh to form a uniform slurry, the particle size range of graphene is 10μm, the aspect ratio is better than 1000, adding n-butanol, adjusting the viscosity, and forming an emulsifiable slurry. The ratio of the graphene resin composite solution is asphalt: phenolic resin: graphene: graphite powder: butanol by weight ratio of 100:50:70:120:40. Prepare a curing agent aqueous solution in a mixing tank, the ratio of the curing agent aqueous solution is deionized water: hexamethylenetetramine: polyvinyl alcohol by weight ratio of 100:4:1. The curing agent aqueous solution is introduced into a high-speed emulsification and dispersion kettle, heated to 90°C, stirred at high speed, and the stirring speed is 25m / s. The prepared 90°C slurry is introduced, and 30 liters of the composite solution is added to 100 liters of the aqueous solution and emulsified. The condensation reaction is carried out for 90 minutes, and the three-dimensional network structure is gradually condensed and solidified to form an insoluble and infusible composite ball. The composite spherical powder wet cake is obtained by centrifugal filtration, and the composite spherical powder is obtained after drying and dispersion at 150°C. The composite spherical powder is carbonized in an inert atmosphere continuous furnace to obtain graphene composite carbon spherical powder. The carbonization temperature is 1200°C, the carbonization time is 120 minutes, and the density of the composite powder is 0.5g / cm 3 , the average particle size is 90μm( Figure 2 ).

[0042] The obtained graphene composite carbon spheres were mixed with nylon 66 at a weight ratio of 1:1, and the hot pressed parts ( Figure 3 ), the density of the flat piece is 0.8g / cm 3 , conductivity is 10S / m, and the conductivity is the same in the thickness and in-plane direction.

[0043] Example 2

[0044] Using the same process equipment, process conditions and raw materials as Example 1, different grades of graphene and formula ratios, the mixing kettle is heated to 90°C, asphalt with a melting point / softening point of 70 to 80°C and thermoplastic phenolic resin, such as Shengquan's phenolic resin, is added, stirred to form a uniform mixed solution, graphene or graphene oxide powder and graphite powder above 800 mesh are added to form a uniform slurry, the particle size range of graphene is 7μm, and the aspect ratio is better than 1000, n-butanol is added, the viscosity is adjusted, and an emulsifiable slurry is formed. The ratio of the graphene resin composite solution is asphalt: phenolic resin: graphene: graphite powder: butanol, the weight ratio is 100:60:100:110:45. A curing agent aqueous solution is prepared in a mixing tank, and the ratio of the curing agent aqueous solution is deionized water: hexamethylenetetramine: polyvinyl alcohol, the weight ratio is 100:5:1. The curing agent aqueous solution is introduced into a high-speed emulsification and dispersion kettle, heated to 90°C, stirred at high speed, and the stirring speed is 25m / s. The prepared 90°C slurry is introduced, and 30 liters of the composite solution is added to 100 liters of the aqueous solution and emulsified. The condensation reaction is 150 minutes, and the three-dimensional network structure is gradually condensed and solidified to form an insoluble and infusible composite ball. The composite spherical powder wet cake is obtained by centrifugal filtration, and the composite spherical powder is obtained after drying and dispersion at 150°C. The composite spherical powder is carbonized in an inert atmosphere continuous furnace to obtain graphene composite carbon spherical powder. The carbonization temperature is 1000°C, the carbonization time is 180 minutes, and the density of the composite powder is 0.45g / cm 3 , the average particle size is 70μm.

[0045] The obtained graphene composite carbon spheres were mixed with nylon 66 at a weight ratio of 1:1 and hot pressed to obtain a flat plate with a density of 0.7 g / cm 3 , conductivity is 20S / m, and the conductivity is the same in the thickness and in-plane direction.

[0046] Example 3

[0047] Using the same process equipment, process conditions and raw materials as Example 1, different grades of graphene and formula ratios, the mixing kettle is heated to 90°C, asphalt with a melting point / softening point of 70 to 80°C and thermoplastic phenolic resin, such as Shengquan's phenolic resin, is added, stirred to form a uniform mixed solution, graphene or graphene oxide powder and graphite powder above 800 mesh are added to form a uniform slurry, the particle size range of graphene is 15μm, and the aspect ratio is better than 1000, n-butanol is added, the viscosity is adjusted, and an emulsifiable slurry is formed. The ratio of the graphene resin composite solution is asphalt: phenolic resin: graphene: graphite powder: butanol is 100:80:60:130:50 by weight. A curing agent aqueous solution is prepared in a mixing tank, and the ratio of the curing agent aqueous solution is deionized water: hexamethylenetetramine: polyvinyl alcohol is 100:6:1 by weight. The curing agent aqueous solution is introduced into a high-speed emulsification and dispersion kettle, heated to 90°C, stirred at high speed, and the stirring speed is 25m / s. The prepared 90°C slurry is introduced, and 30 liters of the composite solution is added to 100 liters of the aqueous solution and emulsified. The condensation reaction is 120 minutes, and the three-dimensional network structure is gradually condensed and solidified to form an insoluble and infusible composite ball. The composite spherical powder wet cake is obtained by centrifugal filtration, and the composite spherical powder is obtained after drying and dispersion at 150°C. The composite spherical powder is carbonized in an inert atmosphere continuous furnace to obtain graphene composite carbon spherical powder. The carbonization temperature is 1000°C, the carbonization time is 180 minutes, and the density of the composite powder is 0.65g / cm 3 , the average particle size is 95μm.

[0048] The obtained graphene composite carbon spheres were mixed with nylon 66 at a weight ratio of 1.5:1, and hot pressed to obtain a flat plate with a density of 1.05 g / cm 3 , conductivity is 150S / m, and the conductivity is the same in the thickness and in-plane direction.

[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0050] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing graphene composite carbon spheres, characterized in that: The graphene composite carbon sphere is an isotropic porous carbon sphere with high thermal conductivity and high electrical conductivity. The raw materials of the graphene composite carbon sphere include: graphene and / or graphene oxide, graphite powder, and adhesive; The adhesive is asphalt and amine-cured heat-shrinkable phenolic resin, which is prepared by emulsification, dispersion, condensation, curing and granulation without template, and then subjected to heating, drying and high-temperature carbonization; The density of the graphene composite carbon sphere is 0.3-1.5 g / cm 3 , the average particle size ranges from 30 to 150 μm.

2. The method for preparing graphene composite carbon spheres according to claim 1, characterized in that: The adhesive raw materials include: butanol, phenolic resin, and asphalt; The raw material formula ratio of the graphene composite carbon ball is asphalt: phenolic resin: graphene or graphene oxide: graphite powder: butanol, and the weight ratio is 100:30-150:50-200:100-200:30-150.

3. The method for preparing graphene composite carbon spheres according to claim 2, characterized in that: The raw material formula ratio of the graphene composite carbon ball is asphalt: phenolic resin: graphene or graphene oxide: graphite powder: butanol, and the weight ratio is 100:40-110:50-110:110-150:40-70.

4. The method for preparing graphene composite carbon spheres according to claim 2, characterized in that: The formula of the emulsified dispersed aqueous solution is: the weight ratio of deionized water: hexamethylenetetramine: polyvinyl alcohol is 100:2-10:0.5-3.

5. The method for preparing graphene composite carbon spheres according to claim 4, characterized in that: The formula of the emulsified dispersed aqueous solution is: the weight ratio of deionized water: hexamethylenetetramine: polyvinyl alcohol is 100: 3-7: 0.5-3; 20 to 40 liters of graphene composite solution are emulsified with 100 liters of aqueous solution.

6. The method for preparing graphene composite carbon spheres according to claim 1, characterized in that: The softening point / melting point of the adhesive asphalt and phenolic resin is 70-80°C, and they can be melted, stirred and evenly mixed together at high temperature; The curing agent of the phenolic resin is hexamethylenetetramine, which is dissolved in deionized water to form an emulsified dispersed aqueous solution, and undergoes a condensation curing reaction with phenolic resin at the emulsified interface during dispersion; The graphene or graphene oxide has a particle size range of 5 to 30 μm, an aspect ratio of better than 1000, and the graphite powder is fine powder with a mesh size greater than 800 meshes.

7. The method for preparing the graphene composite carbon sphere according to claim 6, characterized in that: The graphene or graphene oxide has a particle size range of 7 to 15 mm.

8. The method for preparing graphene composite carbon spheres according to claim 1, characterized in that: The preparation method comprises the following steps: (1) preparing graphene slurry: heating asphalt and thermoplastic phenolic resin to form a mixed solution, adding graphene or graphene oxide powder and graphite powder to form a uniform slurry, adding n-butanol, adjusting the viscosity, and forming an emulsifiable slurry; (2) dissolving polyvinyl alcohol and hexamethylenetetramine in deionized water and stirring uniformly to form a dispersed aqueous solution; (3) introducing the dispersed aqueous solution into a high-speed emulsification dispersion kettle, heating it to 90°C, stirring at a high speed, with the linear speed of the stirring and dispersing disk being greater than 20 m / s, introducing the prepared 90°C graphene slurry, and emulsifying it, adjusting the emulsification conditions, and controlling the emulsified particle size of the slurry. The faster the speed, the smaller the average particle size, and the slower the speed, the larger the average particle size. (4) Continuously stirring at high speed, the phenolic resin gradually condenses and solidifies under the catalytic action of hexamethylenetetramine to form a three-dimensional network structure, forming an insoluble and infusible composite ball, and the condensation reaction time is 60 to 240 minutes; (5) centrifugally dehydrating and filtering to obtain a composite spherical powder wet cake; (6) drying at 150° C. and crushing to obtain composite powder; (7) carbonizing the composite powder in an inert atmosphere furnace to obtain graphene composite carbon powder, the carbonization temperature is 700 to 1500° C., and the carbonization time is 60 to 240 min; (8) The slightly agglomerated composite powder is crushed by a pulverizer to obtain graphene composite carbon spheres with controllable particle size.

9. The method for preparing graphene composite carbon spheres according to claim 5, characterized in that: The production equipment includes industrial-grade mixers, emulsifiers, dehydrators, dryers, carbonization furnaces and pulverizers / crushers to form a large-scale continuous production system.

10. The graphene composite carbon sphere prepared as claimed in claim 5, characterized in that: The graphene composite carbon sphere is compounded with rubber and plastic to improve the electrical conductivity and thermal conductivity, and the electrical conductivity of the composite material compounded with nylon is 5-500 S / m.

Citation Information

Patent Citations

  • Graphite composite carbon electrode material for lead acid battery, electrode prepared from electrode material and preparing method of electrode

    CN104681812A

  • Method for preparing graphene carbon nanotube composite conductive framework for lithium-sulfur battery

    CN108091878A

  • Graphene / phenolic resin high-conductivity nano composite material and preparation method thereof

    CN108117717A

  • Glass carbon graphite block or bar

    CN115650727A

  • Preparation method and application of high-content graphene phenolic resin dispersion

    CN119176957A